Endoscopic ultrasound-guided drainage for local complications related to pancreatitis - Hyung Ku Chon; Seong-Hun Kim (Society of Gastrointestinal Intervention, 2023)
Despite many advances in the treatment of acute pancreatitis, the mortality rate in severe cases is as high as 30%. Therefore, it is very important to treat the local complications of acute pancreatitis. Pancreatic fluid collections (PFCs) are among the most important local complications of acute pancreatitis. According to the Atlanta classification of acute pancreatitis in 2012, PFCs are categorized as acute peripancreatic fluid collections, pancreatic pseudocysts, acute necrotic collections, and walled-off necrosis. In principle, PFCs with complications require an intervention such as drainage. With the recent development of endoscopic ultrasound (EUS)-guided interventions, EUS-guided drainage or necrosectomy has emerged as an important standard treatment for PFCs. In this article, we present recent advances in EUS-guided drainage and necrosectomy for PFCs in acute pancreatitis, along with a literature review.